Дослідження середньовічного м. Губин та його околиць у 2009 р. - Якубовський, В.І. (Археологічні дослідження в Україні, 2010)
Results of 2009 excavations on the territory of the southwestern fortified part of mediaeval Hubyn in Khmelnytsk Oblast and in its suburbs are presented.